Effect of (L.) Webb ex Prantl on Adult Functional Constipation: A Prospective Pilot Study - Rasool Choopani MD, PhD; Anahita Ghourchian MD, PhD; Homa Hajimehdipoor PharmD, PhD; Mohammad Kamalinejad DSc; Fatemeh Ghourchian MD (SAGE Publishing, 2017)
Chronic constipation is a common gastrointestinal disorder that effects an estimated 12% to 30% of general population worldwide. Descurainia sophia L. known commonly as flixweed acts as first-line medical treatment for constipation in Iranian traditional medicine. The aim of this study was to assess the efficacy and safety of this remedy for treating functional constipation by standard assessments. The Rome III criteria for functional constipation were the basis for diagnosis. All participants underwent a 4-week treatment. The primary end point was the proportion of patients achieving ≥3 complete spontaneous bowel movements per week. Secondary outcome measures included Patient Assessment of Constipation-Symptom items, Bristol Stool Form Scale, numbers of laxatives/week used by patients, and reported adverse effects. Thirty-five patients completed the program with no important adverse effect. Fifty-four (4%) patients had ≥3 complete spontaneous bowel movements per week. Descurainia sophia is safe and effective in the treatment of chronic functional constipation.